DS14 is more likely to measure depression rather than a personality disposition in patients with acute coronary syndrome. Issue 6 (3rd September 2015) - Ossola, Paolo; De Panfilis, Chiara; Tonna, Matteo; Ardissino, Diego; Marchesi, Carlo
Abstract : It has been suggested that Type D Personality is a risk factor for acute coronary syndrome (ACS) and the DS14 has been developed for its assessment. However, some of the items on the DS14 seem to evaluate depressive symptoms rather than personality features. Therefore, the present study aims to verify whether an overlap exists between the constructs of Type D Personality and depression. Three‐hundred‐and‐four consecutive patients who were both presenting their first ACS and had no history of major depression completed the Hospital Anxiety and Depression Scale (HADS) and the DS14 to assess Type D personality at baseline and have been re‐evaluated at 1, 2, 4, 6, 9 and 12‐month follow‐ups. Out of 304 subjects (80.6% males), 40 were diagnosed as depressed. An exploratory factor analysis of HADS and the DS14 in the second month revealed that four out of seven items on the depressive subscale of HADS (HADS‐D) and six out of seven items on the Negative Affectivity (NA) subscale of the DS14 segregated on the same factor. Results were verified by a Partial Confirmatory Factor Analysis performed at the twelfth month when most of the patients achieved complete remission from the depressive episode. Temporal stability was poor for NA and Type D Personality and these construct co‐vary with HADS‐D over time. Our data suggests that NA and depression are overlapping constructs, supporting the idea that the DS14 measures depressed features, rather than a personality disposition.